Experimental Studies on the Behaviors of New Energy-Saving Concrete Self-Insulating Load-Bearing Block Wall under Low-Cycle Cyclic Loading. (4th October 2018) - Osman, Bashir H.; Chen, Zhongfan
Abstract : Masonry walls are usually designed to resist the effect of lateral and gravity loads resulting from wind or earthquake excitations. This research aimed at investigating the inelastic behavior of a new energy-saving concrete self-insulating load-bearing block wall (ECSLBW) under in-plane cyclic loading. To provide stronger bond between the concrete block units better than the ordinary concrete masonry units, a new masonry system of concrete blocks with special configurations was made. In this experiment, three new self-insulated block wall specimens were designed, manufactured, and tested. Furthermore, self-supporting structural column-ring beam structure system was used to observe the failure mode of the walls. Moreover, the mechanical properties and seismic indexes of the walls under lateral low-cyclic loading were analyzed, including hysteretic and skeleton curves, stiffness degradation, ductility, and energy losses. The results showed that the new energy-saving block wall can meet the seismic shear calculation under 8-degree rare earthquake and meet the antiseismic fortification target in 8-degree area. Furthermore, self-contained system can greatly improve the seismic shear capacity of the wall. Finally, the seismic shear capacity of the concrete column block masonry was calculated, and the technical application method of block masonry structure was recommended.